MicroRNA sequencing in patients with coronary artery disease - considerations for use as biomarker for thrombotic risk - Chimnonso P. Onuoha; Joseph Ipe; Edward Simpson; Yunlong Liu; Todd C. Skaar; Rolf P. Kreutz (Wiley, 2022)
Abstract MicroRNAs (miRNAs) are small RNAs integral in the regulation of gene expression. Analysis of circulating miRNA levels may identify patients with coronary artery disease (CAD) at risk for recurrent myocardial infarction (MI) after percutaneous coronary interventions (PCIs). Subjects with CAD were selected from the GENCATH cardiac catheterization biobank. Subjects with recurrent MI after PCI were compared with those without recurrent MI during follow‐up in the initial (n = 48) and replication cohort (n = 67). Next generation MiRNA sequencing was performed on plasma samples and whole blood samples fixed with PAXGENE tubes upon collection. Overall, 164 miRNAs derived from whole blood were differentially expressed in the replication cohort between subjects with and without recurrent MI events (p < 0.05), with 69 remaining significant after false‐discovery rate (FDR) correction. None of the miRNAs in plasma was significantly different by FDR among subjects with and without MI. Overall, correlation between direction of effects between plasma and whole blood assays was variable, and only two miRNAs were concordant and significant in both. Associations of miRNA with vascular disease, MI, and thrombosis were further explored. MiRNA profiling has potential as the future biomarker for disease prognosis and treatment response marker in secondary treatment of patients with CAD after PCI. Whole blood may be the preferred sample source as compared to plasma.